Produção de acetato de etila em biorrefinaria: uma análise de viabilidade - Mello Júnior, Dario de Carvalho e (2010)
The study aims to demonstrate the chemical Brazilian industry competitiveness that can be reviewed through the chemical development based on renewable natural resources with high productivity performance, represented here by sugar cane. This study is based on economic competitiveness analysis to produce ethyl acetate, using ethanol as the main raw material, where Brazil is ethyl acetate exporter and in the same time, the Brazilian internal market is strong when compared with others developed countries. Ethyl acetate exported represents 52% of the nameplate Brazilian installed capacity in 2008. There are 3 producers in Brazil, but just one export. All ethyl acetate producers use the same production technology, esterification, made from a reaction between acetic acid and ethanol. That acetic acid is widely imported by the biggest ethyl acetate exporter. The assumption used by this study is that the ethyl acetate competitiveness is given by ethanol, where it is produced by fermentation of the sugar cane juice, in Brazil. Now the esterification technology applied is well known worldwide and the acetic acid is a petrochemical commodity that follows the international price. So Brazil is an ethyl acetate exporter player because of the ethanol competitiveness, that it is produced from sugar cane. Moving to ethanol deshydrogenation technology we can produce ethyl acetate using only ethanol as raw material, reducing the importation requirements of acetic acid, that it represents an annually reduction around of 0,5 billion dollars in the Brazilian petrochemical trade balance and getting a ethyl acetate more competitive that is currently produce here in Brazil. From this study on we can think about others chemical products that could be produced from the sugar cane matrix, like, ethylene, plastics, lubricants etc., creating a new reference for the chemical Brazilian industry and reducing the current dependency of oil and natural gas.